The Impact of The Flu in an Internal Medicine Ward in Portugal: A Retrospective Case Series - Barata, Beatriz; Eça, Rosário; Sampaio, Beatriz; Urmal, Inês; Leal, Mafalda; Lalanda, Carlota; Pina Pereira, Ana Catarina; Rebelo, Maria; Salsinha Frade, Jorge; Margarido, Elisabete (International Journal of Innovative Research in Medical Science, 2024)
Influenza is a sudden-onset viral illness that mainly affects the respiratory tract. Worldwide, it is responsible for 3 to 5 million cases of serious illness and up to 650.000 deaths per year. Annual vaccination is the main method of prevention and should be targeted at high-risk population groups. This retrospective study’s objective was to characterize the cases with a positive test for the influenza virus in nasopharyngeal exudate in an internal medicine ward and its risk factors. It was based on consultation of the medical records of patients hospitalized in the 2018/19 flu season, with evaluation of clinical, demographic and vaccination characteristics, the type and strain of Influenza virus, duration of hospitalization, need for oxygen therapy, use of antivirals and antibiotics and death rate. 52 patients were included, predominantly female (61.5%), with a mean age of 79.6 years. 92.3% had at least one comorbidity (in decreasing frequency: cardiovascular disease, lung disease, diabetes mellitus, cancer, immunosuppression, chronic kidney disease, obesity and liver disease). Influenza A virus was identified in all patients and of these (H3N2 in 71% and H1N1 in 15%). Only a minority (13.5%) of patients were vaccinated. Over a third of the patients had bacterial superinfection. In one fifth, antibiotic therapy was started in the emergency room but later suspended due to poor conviction of superinfection. The majority of patients (88.5%) had respiratory failure; 7.5% worsened kidney function and 2% worsened liver function. 94% of patients were medicated with oseltamivir and of these, 17% were able to complete the cycle on an outpatient basis. Mortality was 7.7%. In conclusion, the vaccination rate in the population studied was much lower than desired. The inappropriate use of antibiotic therapy in the emergency room was also noteworthy, sometimes without clear suspicion of bacterial superinfection.